G405 Defining healthcare professional competence for working with teenagers and young adults with cancer – a brightlight study. (27th April 2015) - Taylor, RM; Aslam, N; Feltbower, R; Raine, R; Whelan, JS; Gibson, F
Abstract : Aims: Teenage and young adult (TYA) medicine is emerging as a distinct speciality, acknowledging the core tasks required to enable a young person to transition successfully to adulthood. As healthcare education is subdivided into adult or child focused-training, a framework is needed to reflect the specific competencies required to care for this population. The aim was to provide international consensus on the competencies required by healthcare professionals to provide specialist cancer care for TYA. Methods: A modified, international e-Delphi survey was conducted over 2 rounds. Experts were defined as professionals having worked in TYA cancer care for more than 12 months. They were identified through publications and invitations via professional organisations. The content of round 1 was informed by UK pilot work and a workshop undertaken by the professional organisation, TYAC. There were 87 closed-ended questions with responses on a 9-point Likert scale and further open-ended responses to identify other skills, knowledge and attitudes. Round 2 contained only items with no consensus in round 1 and suggestions of additional items of competency. Consensus was defined as a median score ranging from 7–9. Results: A total of 179 registered to be members of the expert panel, of which valid responses were available for 158 (88%) in round 1 and 136 (86%) for round 2. The majority of participants were nurses (35%) or doctors (39%) from Europe (55%) or North America (35%). All 87 items in round 1 reached consensus with an additional 15 items identified for round 2. The most important skill was reported as "being able to identify the impact of disease on young people's life"; the most important area of knowledge was "know about side-effects of treatment and how this might be different to those experienced by children or older adults"; "ability to talk about difficult issues" was the most important communication skill and honesty the highest rated attitude. Conclusions: The process has been successful in identifying a high degree of consensus for competencies and skills to be used of training for professionals working with TYA.